Penggunaan Media Pembelajaran Film Animasi untuk Peningkatan Kemampuan Berbicara Anak Usia 4-5 Tahun di TK YPRU Mataram - Guruh Rizky Firdaus; Gunawan Gunawan; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2022)
Animated film learning media is an interesting learning media to improve the speaking skills of children aged 4-5 years, learning media which are basically two-dimensional animations that move and learning attracts more students' attention. This study aims to determine the use of animated film learning media for the speaking ability of children aged 4-5 years at YPRU Mataram Kindergarten. This study used a qualitative descriptive study with 13 children as subjects. Data is collected through observation and documentation. The data analysis technique used in this research is descriptive qualitative. The steps in starting research activities using animated film media are as follows: First, provide media that will be used for learning. Second, make sure the child's position is comfortable when watching. Third, ask children to focus on animated films. Fourth, do question and answer. The results of the study in improving speaking skills, there are 6 indicators used, in the first indicator 2 children are starting to develop (MB), 3 children are developing (B) and 8 children are developing very well (BSB), the second indicator is 2 children are starting to develop (MB), 4 children are developing (B), 7 children are developing very well (BSB), the third indicator is 1 child not yet developing (BB), 4 children are starting to develop, 7 children are developing (B), the fourth indicator is 2 children starting to develop (MB), 6 children developing (B), 5 children developing very well (BSB), the fifth indicator 9 children developing (B), 4 children developing very well (BSB), the sixth indicator 1 child has not developed (BB), 2 children are starting to develop (MB), 4 children are developing (B), 6 children are developing very well (BSB) 3 children are categorized as starting to develop (MB), 4 children are categorized as developing (B), and 6 children are categorized as developing very well (BSB). The conclusion in this study of 13 children, 3 children started to develop (MB), 4 children developed (B) and 6 children developed very well (BSB).